Inquiry Ability Profile of SMAN 8 Pontianak Students on Salt Hydrolysis Subject Material - Alaida, Fifi; Erlina, Erlina; Lestari, Ira; Sahputra, Rachmat; Ulfah, Maria (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The inquiryÂ ability is an ability to obtain information through observation or experimentation to solve a problem by using critical and logical thinking skills which include several stages, namely the stages of formulating problems, formulating hypotheses, analyzing data, and concluding. This study aimed to determine studentâ€™s ability to inquire about the salt hydrolysis material at SMAN 8 Pontianak. The type of research used is descriptive research using the case study method. The research subjects were 20 students of class XI science at SMAN 8 Pontianak. The instrument used is an inquiry-ability test in the form of 4 essay questions and interview guidelines as a supporting instrument. The results showed that the average ability to inquire of students was included in the good category. The results of the analysis on each aspect stated that the average student inquiry ability in the aspect of formulating problems obtained a value of 80.6% and was classified as a good category. The aspect of formulating a hypothesis has an average value of 73% with a good category. The aspect of analyzing the data has a value of 55.8% with a fairly good category. While the aspect of formulating conclusions has a value of Â 60.6% with a fairly good category.